Gut Microbiota Dysbiosis and Its Impact on Type 2 Diabetes: From Pathogenesis to Therapeutic Strategies - Yonghua Yu; Yilan Ding; Shuangyuan Wang; Lei Jiang (Metabolites)
Type 2 diabetes mellitus (T2DM) is a common metabolic disorder characterized by insulin resistance and pancreatic β-cell dysfunction. Emerging evidence indicates that gut microbiota dysbiosis may contribute to the development of T2DM. Individuals with T2DM exhibit notable changes in gut microbiota composition, including shifts in the balance between Firmicutes and Bacteroidetes, a reduction in butyrate-producing bacteria, and an increase in opportunistic pathogens. Gut microbiota-derived metabolites—such as short-chain fatty acids, bile acids, and amino acids—have been implicated in the pathogenesis of T2DM, highlighting the critical role of host-microbe interactions. In this overview, we discuss the gut microbiota dysbiosis associated with T2DM and explore the molecular links between microbiota-derived metabolites and the pathogenesis of diseases. Additionally, we explore potential therapeutic strategies, including probiotics and dietary interventions, to modulate the gut microbiota and its metabolites, providing insights for future clinical research and the development of novel treatments for T2DM.